Successful Anaesthetic Management of a Patient with Post Burn Contracture and Difficult Airway: A Case Report - Rahman, Mushfiqur; Rahman, Md Khalilur (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
The Anaesthetic management of patients with post burn contracture release poses many problems toanaesthesiologist. Airway management in such cases is still challenging to anaesthesiologist as thecontracture and deformity due to fibrous tissue resulting in non-alignment of oral, pharyngeal andlaryngeal planes, makes laryngoscopy and endotracheal intubation very difficult or impossible and thiscan result in many life threatening and serious complications. We report the successful airway managementof a patient with restricted neck extension and fixed flexion deformity by Laryngeal mask airway (LMA)followed by endotracheal intubation. JBSA 2020; 33(2): 107-110